A rapid direct-differential agglutination assay for Brucella detection using antibodies conjugated with functionalized gold nanoparticles - Hans, Richa; Yadav, Pranjal Kumar; Zaman, M. Burhanuz; Poolla, Rajaram; Thavaselvam, Duraipandian (Frontiers in Nanotechnology, 2023)
Brucellosis is the most widespread and serious zoonotic disease worldwide which affects livestock, sylvatic-wildlife, marine dwellers and inhabiting humans. It is acquired by alpha-proteobacteria which belongs to genus Brucella and categorized as the potential bio-threat agent. In this study, we have developed a rapid and direct differential whole cell (WC) agglutination based assay for its on-field detection. The recombinant outer membrane (rOmp28) protein derived specific mice IgG polyclonal antibodies (pAbs) of Brucella were purified using affinity chromatography and conjugated with functionalized gold nanoparticles (AuNPs) for rapid agglutination. A positive blot of 32 kDa protein revealed specific immuno-reactivity of rOmp28-pAbs using immuno-blot analysis. For synthesis of AuNPs, conventional ‘Turkevich Method’ was optimized at a concentration < 1 mM of gold precursor for obtaining 50 nm size particles. And, their physico-chemical characteristics were analysed using UV-Visible Spectrophotometry, Fourier Transform Infra-Red Spectroscopy (FT-IR), Raman Spectroscopy, X-Ray Diffractions (XRD), Scanning Electron Microscopy (SEM), Transmission Electron Microscopy (TEM), Dynamic Light Scattering (DLS), Zeta Potential (ζ, ZP) and Fluorescence Spectroscopy. Further, these AuNPs were functionalized with N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride (EDC) and N-hydroxysuccinimide (NHS) to prepare the modified carboxylated AuNPs. For bioconjugation with Brucella rOmp28 IgG pAbs, antibody-conjugated functionalized AuNPs constructs were prepared and characterized with FT-IR analysis having strong N-H deformations. Subsequently, these bioconjugated AuNPs were used in developing direct-differential slide agglutination assay with detection limit of 104 CFU mL-1. The sensitivity of this assay was compared with standard double-antibody sandwich ELISA (S-ELISA) using rOmp28 IgG pAbs with LOD of 103 CFU mL-1 at the detection range of 102 to 108 CFU mL-1. No intra-species cross-reactivity was observed on the evaluation of its specificity with a battery of closely related bacterial species. In conclusion, the increased sensitivity and specificity of the developed agglutination assay obtained using bioconjugated functionalized AuNPs is ≥ 98% for the detection of Brucella. Therefore, it can be used as an alternate rapid method of direct WC detection of bacteria for being simple, robust and cost-effective with minimal time of reaction in case of early disease diagnosis.